The investor's manifesto : preparing for prosperity, Armageddon, and everything in between - Bernstein, William J. (Wiley, 2010)
With the current market maelstrom as a back-ground, this timely guide describes just how to plan a lifetime of investing, in good times and bad, discussing stocks and bonds as well as the relationship between risk and return.